English dictionaries as cultural mines - Facchinetti, Roberta, 1967- (Cambridge Scholars, 2012)
Discusses "the role of dictionaries in the identification and expression of cultural aspects in language, with special reference to English. As such, its eleven chapters have been arranged to focus on general, genre-specific, monolingual and bilingual lexicography, both from a diachronic and a synchronic perspective"--Cover, page [4].